Pretrial Release Data, 1969 - Nagel, Stuart S. ([Verlag nicht ermittelbar], 1984)
This data collection contains information gathered about pretrial release policies, procedures, and outcomes in a 1969 survey of police chiefs, judges, prosecutors, defense attorneys, and bail project directors in 72 cities across the United States (with a higher proportion in Illinois). The research objectives included: (1) developing a model designed to determine the optimum percentage of defendants to hold prior to trial, (2) developing a model designed to make decisions on whether a defendant should be released or held in jail prior to trial, (3) comparing cities having bail reform projects with cities not having them, (4) comparing cities that required arrested persons to provide 10 percent of the bond with cities requiring 100 percent of the bond, and (5) determining the causes and effects of variations across cities in the percentage of defendants held in jail prior to trial. The survey focused on the processing of arrested persons prior to trial. Respondents answered questions about the organization and procedures in pretrial release, supplied approximate statistical data (e.g., percent of arraigned individuals who were released prior to their trial and failed to appear in court for their trial), estimated statistical trends in pretrial release during the previous five years, reported on attitudes in their communities toward administration of bail, rated the importance of several criteria when determining if a defendant was to be allowed pretrial release, and indicated whether their city had a bail reform program, and if so, its characteristics. Demographic data (ranging from population to income to crime rates) about the 72 cities represented in the survey are also included in the file.